2023
DOI: 10.1002/adfm.202212738
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine‐Integrated Nanointerface between Fibrillar Matrix and Hydrophilic Nanohydroxyapatite Regulates Immune Microenvironment to Boost Endogenous Bone Regeneration

Abstract: Driving endogenous bone regeneration by cell‐ and factor‐free biomaterials is the most ideal repair strategy. Herein, hybrid interleaved scaffold (HDSH) with nanosized interfacial integration is assembled by organic/inorganic interactive bonding at the nanoscale. With the help of transcriptome and proteome analysis, the regenerative mechanism of this scaffold is elaborated at the molecular level, which confirms that this strategy recreates a suitable immune microenvironment (anti‐inflammatory and M2‐polarizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…[39,41] Finally, our newly reported research had proved that dopamine-integrated nanointerface between fibrillar matrix and nHAp could drove functional cells/cytokine adhesion, inchoate vascularization, and greatly enhance endogenous stem cell recruitment to initiate robust osteogenesis. [52] Hence, the photointegrated interface binding and dopamine-mediated multiple chemical reactions in HGel-g-nHAp might contribute to ESCs recruitment and provide a biomimetic niche for stem cells to guide early osteogenesis and stimulate rapid vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…[39,41] Finally, our newly reported research had proved that dopamine-integrated nanointerface between fibrillar matrix and nHAp could drove functional cells/cytokine adhesion, inchoate vascularization, and greatly enhance endogenous stem cell recruitment to initiate robust osteogenesis. [52] Hence, the photointegrated interface binding and dopamine-mediated multiple chemical reactions in HGel-g-nHAp might contribute to ESCs recruitment and provide a biomimetic niche for stem cells to guide early osteogenesis and stimulate rapid vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…These results were supported by a previous study showing that the introduction of DA-and PDA-based structures, as well as MXene, was very useful for scavenging to maintain intracellular redox homeostasis, which can also be strengthened by local photothermal treatment. [56,57] Implantable biomaterials with dual capabilities to regulate the proportion of M1/M2 macrophages and alleviate inflammation are indispensable for bone healing. Related studies have demonstrated that the expression of a large number of M2 phenotype macrophages during bone healing has a promoting effect on efficient bone repair and vascular regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…These results were supported by a previous study showing that the introduction of DA‐ and PDA‐based structures, as well as MXene, was very useful for scavenging to maintain intracellular redox homeostasis, which can also be strengthened by local photothermal treatment. [ 56,57 ]…”
Section: Discussionmentioning
confidence: 99%
“…Though exogenous cells and growth factors are key regulators of each stage for accelerating bone healing, the unpredictable clinical risk has been constraining their transformation application . In the previous works, we demonstrated that endogenous stem cells (ESCs) were successfully recruited in situ to promote early osteogenesis and quick vascularization in cell/factor-free scaffolds with improved material designs, as well as integrating type I collagen (Col I) fibrillar matrices and hydroxyapatite (HAP) by the hybrid cross-linking mechanism mediated by dopamine-modified hyaluronic acid (HAD) . However, the closed pore walls and the long distance between pores in the scaffold generally restrict the cells’ migration.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier research has demonstrated that adding polyphenols, like dopamine (DA), may control how Col I, HA, and HAP’s hybrid cross-links are integrated at the interface. , DA has long been regarded as a crucial adhesion functional group . The catechol group and lysine residues are present in DA, a substance that is prevalent in both plants and animals, and it has the same outstanding adhesion properties as -3,4-dihydroxyphenylalanine (DOPA), which is found in naturally occurring mussels .…”
Section: Introductionmentioning
confidence: 99%